2008
DOI: 10.1136/jech.2007.065169
|View full text |Cite
|
Sign up to set email alerts
|

High agreement on family affluence between children's and parents' reports: international study of 11-year-old children

Abstract: Young adolescents' self-reports of family affluence are fairly valid across the six countries. This finding suggests that the variables measured can be used in epidemiological studies that aim at ranking children according to socioeconomic position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 13 publications
2
79
0
2
Order By: Relevance
“…It has been reported that the FAS II items showed a higher completion rate than items on parental education and occupation (Boudreau and Poulin 2009;Lin 2011;Molcho et al 2007). Validation studies of the FAS II have been done in many HBSC member countries as well as some non-HBSC member countries, from which the results showed that the FAS II items have a moderate internal reliability (Lin 2011;Molcho et al 2007;Wardle et al 2002), a significant association with parental education and occupation (Currie et al 1997;Molcho et al 2007), a high agreement rate between adolescents and parents (Andersen et al 2008), and a satisfactory correlation with the national wealth indicator, Gross Domestic Product (GDP) . Although the test-retest reliability of FAS II items has not been examined, the rather higher agreement can be predicted due to the objectivity and stability of the indicators .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the FAS II items showed a higher completion rate than items on parental education and occupation (Boudreau and Poulin 2009;Lin 2011;Molcho et al 2007). Validation studies of the FAS II have been done in many HBSC member countries as well as some non-HBSC member countries, from which the results showed that the FAS II items have a moderate internal reliability (Lin 2011;Molcho et al 2007;Wardle et al 2002), a significant association with parental education and occupation (Currie et al 1997;Molcho et al 2007), a high agreement rate between adolescents and parents (Andersen et al 2008), and a satisfactory correlation with the national wealth indicator, Gross Domestic Product (GDP) . Although the test-retest reliability of FAS II items has not been examined, the rather higher agreement can be predicted due to the objectivity and stability of the indicators .…”
Section: Introductionmentioning
confidence: 99%
“…The FAS is constructed as a 0-7 point scale with lower scores representing lower levels of affluence and vice versa. The FAS was collected in eight categories ranging from 0 to 7, which were recoded into 3 groups for the analysis, low: 0-3, intermediate: 4-5 and high: 6-7 [14]. Participants were also asked to indicate how difficult they found the TTO task was to complete on a scale from 1 to 4 where 1 indicates 'not difficult' and 4 indicates 'very difficult'.…”
Section: /(mentioning
confidence: 99%
“…Socio-economic status was measured by applying the Family Affluence Scale (FAS), a measure of socioeconomic position designed for young person self-report [14]. The FAS is constructed as a 0-7 point scale with lower scores representing lower levels of affluence and vice versa.…”
Section: /(mentioning
confidence: 99%
“…When the four indicators are combined to produce a linear composite score, the family affluence scale ranges from zero (lowest affluence) to nine (highest affluence). The scale has been validated as reflecting the material resources of the family (Andersen et al, 2008).…”
Section: Family Affluence Scale (Fas)mentioning
confidence: 99%